MINERALS OF RARE EARTH ELEMENTS IN THE PHOSPHATE FRACTION OF FERROMANGANESE CRUSTS ON SEAMOUNTS - Baturin G.N.; Dubinchuk V.T.; Azarnova L.A.; Mel'nikov M.E. (My University, 2006)
Ferromanganese crusts on seamounts are among the major forms of solid fossil minerals in the ocean. They contain a significant amount of nonore inclusions, including calcium phosphates that often represent the crust-underlying and closely associated substrate. Phosphate is an undesirable impurity in ores, on the one hand, and an independent form of chemical raw material containing not only phosphorus, but also rare earth elements (REE) and several other valuable components, on the other hand.